Evaluation of Neurological Manifestations of Systemic Lupus Erythematosus - Rasheed, Ahmed A.; Shalal, Ghayath A.; Hussein, Sadiq M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Neuropsychiatric symptoms are typical consequences in patients with systemic lupus erythematosus (SLE). There is no apparent link between the clinical parameters of SLE patients and the development of neuropsychiatric symptoms.Objectives: to determine the incidence of neurological manifestations and the risks associated with them in SLE patients.Patients and Methods: This is a case-series study comprised of 65 patients who visited the rheumatology department at Baghdad Teaching Hospital/Medical City between January 2022 and February 2023. All patients' demographic and clinical data, including age, gender, disease duration, type and duration of treatment, general signs of the disease, and neurological and psychiatric manifestations of SLE, were collected. Laboratory data comprised plasma anti-phospholipid antibodies (aPL), anti-double-stranded DNA (anti-dsDNA), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). The cognitive dysfunction was assessed using the six-item cognitive impairment test (6CIT).Results: Out of 65 patients, 34 (52.3%) were found to have at least one neuropsychiatric SLE (NPSLE) manifestation. Headache and depression were the most common NPSLE manifestations encountered in 36 patients (55.4%), followed by psychosis (21.5%), neuropathy (16.9%), and stroke and seizure (13.5%). In multivariate analysis, each of age > 35 years (OR= 2.92, 95%CI= 1.12-34.2 0.10), disease duration > 5 years (4.45, 95% CI = 1.23-28.43, p= 0.001), anti-phospholipid Abs (OR= 4.22, 95%CI= 1.17-89.38), lupus nephritis (OR= 6.34, 95% 1.27- 64.98) and 6CIT > 3 (OR = 5.83, 95% CI = 1.55-21.87) are independent predictors for NPSLE in patients with SLE.Conclusions: Neuropsychiatric manifestations developed in more than half of the SLE cases studied within up to six years of disease duration. Headache and depression, psychosis, and neuropathy are the most common NPSLE manifestations. Older age and longer disease duration are risk factors for the development of NPSLE. Clinically, anti-phospholipid antibodies, lupus nephritis, and a high score of the six-item cognitive impairment test (>8) are predictors for NPSLE.